Role of serial multiparametric magnetic resonance imaging in prostate cancer active surveillance - Vos, Larissa J (World J Radiol, 2016)
AIM: To examine whether addition of 3T multiparametric magnetic resonance imaging (mpMRI) to an active surveillance protocol could detect aggressive or progressive prostate cancer. METHODS: Twenty-three patients with low risk disease were enrolled on this active surveillance study, all of which had Gleason score 6 or less disease. All patients had clinical assessments, including digital rectal examination and prostate specific antigen (PSA) testing, every 6 mo with annual 3T mpMRI scans with gadolinium contrast and minimum sextant prostate biopsies. The MRI images were anonymized of patient identifiers and clinical information and each scan underwent radiological review without the other results known. Descriptive statistics for demographics and follow-up as well as the sensitivity and specificity of mpMRI to identify prostate cancer and progressive disease were calculated. RESULTS: During follow-up (median 24.8 mo) 11 of 23 patients with low-risk prostate cancer had disease progression and were taken off study to receive definitive treatment. Disease progression was identified through upstaging of Gleason score on subsequent biopsies for all 11 patients with only 2 patients also having a PSA doubling time of less than 2 years. All 23 patients had biopsy confirmed prostate cancer but only 10 had a positive index of suspicion on mpMRI scans at baseline (43.5% sensitivity). Aggressive disease prediction from baseline mpMRI scans had satisfactory specificity (81.8%) but low sensitivity (58.3%). Twenty-two patients had serial mpMRI scans and evidence of disease progression was seen for 3 patients all of whom had upstaging of Gleason score on biopsy (30% specificity and 100% sensitivity). CONCLUSION: Addition of mpMRI imaging in active surveillance decision making may help in identifying aggressive disease amongst men with indolent prostate cancer earlier than traditional methods.